Reseña del libro: Barrajón López, E. (2024). Sujeto y predicado: concordancia y discordancias - Sergio Martínez Moreno (Estudios de Lingüística)
Barrajón López, E. (2024). Sujeto y predicado: concordancia y discordancias. Arco/Libros. 80 páginas, ISBN 9788471339447.